Contentment and tranquility: Exploring their similarities and differences. Issue 2 (4th March 2019) - Berenbaum, Howard; Huang, Alice B.; Flores, Luis E.
ABSTRACT: Two studies explored the similarities and differences between contentment and tranquility. In Study 1, in a sample of college students (N = 154), we examined the degree to which contentment and tranquility were associated with different types of pleasurable activities. Whereas contentment was positively associated with mastery activities, tranquility was negatively associated with mastery activities. Tranquility was strongly positively associated with spiritual activities. In Study 2, in a sample of college students (N = 176), using both trait and daily diary assessments, we examined the degree to which contentment and tranquility were associated with the degree to which participants focused on the process–versus the outcome–of activities, as well as their level of acceptance. Both contentment and tranquility were positively associated with acceptance. Tranquility was also positively associated with a focus on process. Based on the results of the present research, we update our theories about contentment and tranquility.